A bio-inspired design strategy for easy powder removal in powder-bed based additive manufactured lattice structure. Issue 3 (3rd July 2022) - Verma, Saurav; Kumar, Ajeet; Lin, Shang-Chih; Jeng, Jeng-Ywan
ABSTRACT: This study evaluates the challenges of powder removal inside surface-based lattice structures that have been fabricated by the polymer-powder-based additive manufacturing (AM) process. The natural flow adaptations of plant cells' morphology and perforation that allow water and minerals easy transport have been bio-mimicked for ease of powder flow during post-processing powder removal. Vessel-shaped and supportless lattice structures with ventilations have been designed, followed by a Computational fluid dynamics (CFD) simulation. This is to study the fluid flow pattern and turbulence inside the lattice structures. The designed lattice structures were 3d printed with polyamide 12 (PA-12) material by HP-MJF 4200 powder bed technology. They were followed by powder removal using a pressurised air gun and computerised tomography (CT-scan) to observe the regions of trapped powder inside the lattice structures. The uni-axial compression tests were conducted to observe the effect of ventilation on the mechanical properties of the lattice structures.